Water hyacinth char addition in iron ore pellet: An exploratory study - Gupta R.C.; Gautam J.P.; Mohan S. (My University, 2025)
The utilization of water hyacinth as an additive in the preparation of iron ore pellets was investigated. The prepared pellets, fired for particular time and temperature, were tested via cold crushing strength (CCS) examination. The water hyacinth char was found to strengthen the crushing behavior of pellets during heating, and hence its use as a potential additive was recommended.